2012
DOI: 10.1108/02656711211245674
|View full text |Cite
|
Sign up to set email alerts
|

Minding the contexts of mindfulness in quality management

Abstract: PurposeThe purpose of this paper is to point out the potential for further theorizing of the concept of mindfulness, by extending and nuancing present accounts of East‐West dichotomies in relation to the concept.Design/methodology/approachThe paper takes the form of a literature review.FindingsDichotomies of Western and Eastern approaches to mindfulness can be extended by analyzing key elements of their respective philosophies, notably through their different views on permanence versus impermanence, uni‐direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The concept of mindfulness draws from many philosophical and psychological backgrounds such as the ancient Greek philosophy and phenomenology (Ndubisi, 2014). Much of the existing mindfulness research is in the fields of psychology, sociology, and education (e.g., Capel, 2012;Demick, 2000;Langer, 1989;Langer & Moldoveanu, 2000); entrepreneurship and creativity (Reilly, Lilly, Bramwell, & Kronish, 2010;Rerup, 2005); marketing (Ndubisi, 2012(Ndubisi, , 2014Sheth, Sethia, & Srinivas, 2011); information systems and communication (Butler & Gray, 2006;Timmerman, 2002); business and interpersonal relationships (Burgoon, Berger, & Waldron, 2000;Saavedra, Chapman, & Rogge, 2010); quality and reliability (Bjurström, 2012;Ndubisi, 2012b); and strategy (Bayraktar & Ndubisi, 2014;Weick & Sutcliffe, 2006) are experiencing a growing application of the theory. The concept of mindfulness is complex.…”
Section: Mindfulnessmentioning
confidence: 99%
“…The concept of mindfulness draws from many philosophical and psychological backgrounds such as the ancient Greek philosophy and phenomenology (Ndubisi, 2014). Much of the existing mindfulness research is in the fields of psychology, sociology, and education (e.g., Capel, 2012;Demick, 2000;Langer, 1989;Langer & Moldoveanu, 2000); entrepreneurship and creativity (Reilly, Lilly, Bramwell, & Kronish, 2010;Rerup, 2005); marketing (Ndubisi, 2012(Ndubisi, , 2014Sheth, Sethia, & Srinivas, 2011); information systems and communication (Butler & Gray, 2006;Timmerman, 2002); business and interpersonal relationships (Burgoon, Berger, & Waldron, 2000;Saavedra, Chapman, & Rogge, 2010); quality and reliability (Bjurström, 2012;Ndubisi, 2012b); and strategy (Bayraktar & Ndubisi, 2014;Weick & Sutcliffe, 2006) are experiencing a growing application of the theory. The concept of mindfulness is complex.…”
Section: Mindfulnessmentioning
confidence: 99%
“…The first component consists in focusing full attention on immediate experience. [37][38][39][40][41] In addition, studies in the realm of business have found mindfulness to be beneficial in improving service quality in small to medium employers, 42 relationship quality in service employers, 43 marketing strategy, 44 quality and reliability in small and large employers, 45 quality management, 46 product failure management, 47 task performance, 48 employee turnover intentions, 49 and resonant leadership. In theory, this process of nonevaluative, nonjudgmental awareness of present moment experience allows for a detachment from ruminative and elaborate thought patterns regarding those experiences.…”
mentioning
confidence: 99%
“…Perhaps more specifically to the business environment is the notion that mindfulness increases our appreciation for and understanding of multiple perspectives, openness to new information and the creation of new categories for learning, and greater adaptation to constantly and rapidly changing environments (Bjurström 2012;Dane 2011;Marques 2010). All of these aforementioned benefits in and of themselves are undoubtedly valuable in an intense, dynamic business environment.…”
Section: Mindfulness: Benefits and General Applicationsmentioning
confidence: 99%